A bright future for proteomics of health and disease. Introduction to the US HUPO 2021 themed issue – proteomics from single cell to systems biology in health and disease. (28th September 2022) - Pino, Lindsay; Banarjee, Reema; Basisty, Nathan
Abstract : Lindsay Pino, Reema Banarjee and Nathan Basisty introduce the Molecular Omics themed issue on proteomics from single cell to systems biology in health and disease. Abstract : In this themed issue of Molecular Omics, in partnership with the U.S. Human Proteome Organization, we are proud to present the latest research featured at the 17th Annual US HUPO conference: Proteomics from Single Cell to Systems Biology in Health and Disease. This issue is a testament to the continuing contributions of proteomic research, particularly the application of modern mass spectrometry-based proteomic workflows, to the advancement of our understanding of the underlying human biology and mechanisms of disease.